Aplicação da matriz de análise multicritério na seleção e priorização de projetos inovadores na área de pesquisa e desenvolvimento de produtos (P&D) de uma empresa de construção civil - Brescovit, Silvio Jose (Universidade do Vale do Rio dos Sinos, 2016)
Building construction has a great financial importance on Brazil’s economic scenario. It is acknowledge for getting large investments and for having high levels of materials and time waste (Schwengber, 2015). It is a sector characterized by informal employment, handcraft-building systems, low levels of industrialization and skilled labor. Therefore, there are great opportunities development in this area, especially on construction management, industrialization and innovation of building systems. For this reason, it justified a study of management tools applied in the construction sector. Whence, this article presents a case study using a Multicriteria Analysis Tool on research and development (R & D) innovation projects management of a specific construction company. Also as part of this work a practical assessment of the effectiveness of using this tool in the evaluation of these projects, comparing the results found in an array with company real scenario.
Keywords: Construção civil; Gestão de projetos; Matriz análise multicritério; Pipeline; Building construction; Project management; Multicriteria matrix analysis